EVALUASI KEBIJAKAN PENGELOLAAN PEMAKAMAN DI KOTA SEMARANG ( Studi Kasus Pengelolaan TPU Bergota Tahun 2012) - Zanuari Agung N (Journal of Politic and Government Studies, 2013)
ABSTRACTThe title of this thesis is the Cemetery Management Policy Evaluation in the city of Semarang (Parks Cemetery Management Case Study Bergota Year 2012). This study aimed to compare by describing the implementation of the Regulation on the funeral of Semarang District which includes processes, goals, and achievements of the organization of the funeral events. In addition, this study also aims to identify the obstacles encountered in the implementation of the cemetery, and to know the distortion or misuse contrary to Bylaw No. 10 Year 2009 on concerning Funeral and Cemetery Levy's body.The method used in this research is a qualitative research method. In the technique of data collection is done by conducting interviews with sources involved in organizing the management of the cemetery, the collection of documents, and observations by observing firsthand how the process of the funeral in the cemetery Bergota. Processing the data in this study using data analysis as outlined descriptively.These results indicate that the policy of Regulation No. 10 Year 2009 on the Implementation of Funeral and Cemetery levies imposed by government bodies Semarang include appropriate policies as a reference implementation of a funeral in the city of Semarang. but in the process of implementing those policies not run optimally because there are still some obstacles such as: is the lack of public understanding about the policy. This is due to suboptimal socialization process from the city of Semarang, making it appear new problems in the form of distortions or deviations from the public, as are the buildings around the cemeteries (Bergota Parks Cemetery) and the failure of communities to conduct the funeral registrasi.dalam giving rise to a wild collection.From these results, it can be concluded that the policy of Bylaw No.. 10 Year 2009 on the Implementation of Funeral and Cemetery levies imposed by government bodies Semarang includes the right policy, but in the process of implementing the government Semarang less than optimal because there are still some obstacles and problems.Keywords: Policy, Funeral, Bergota Parks Cemetery, Semarang City Government